Exploiting heat transfer to achieve efficient photoelectrochemical CO2 reduction under light concentration. Issue 5 (8th April 2022) - Kistler, Tobias A.; Um, Min Young; Cooper, Jason K.; Sharp, Ian D.; Agbo, Peter
Abstract : Photoelectrochemical carbon dioxide reduction to carbon monoxide at 16% solar-to-fuel conversion efficiency is achieved via electrolyte cooling. Abstract : Photoelectrochemical (PEC) conversion of carbon dioxide into valuable chemicals and fuels represents a promising path towards combating anthropogenic CO2 emissions. However, the limited conversion efficiencies, operation lifetimes and CO2 utilization efficiencies of PEC devices currently prohibit their application beyond the laboratory scale. Here, a wireless device converting CO2 and water into carbon monoxide and hydrogen at a peak solar conversion efficiency exceeding 16% under an illumination intensity of 5 suns is demonstrated. A CO/H2 product ratio between 10–20 is measured during a 17 h stability test. Fluctuations in device performance are rigorously analyzed via deconvolution of electrochemical and photoabsorber contributions. It is demonstrated that beneficial heat dissipation is enabled by wireless integration of the photoabsorber and electrocatalyst components, accounting for roughly 10% of the achieved conversion efficiency, an achievement unattainable with physically separated photoabsorber and electrolyzer components.